Facile fabrication of BiVO4 nanofilms with controlled pore size and their photoelectrochemical performances. Issue 48 (24th November 2015) - Feng, Chenchen; Jiao, Zhengbo; Li, Shaopeng; Zhang, Yan; Bi, Yingpu
Abstract : We demonstrated a facile method for the rational fabrication of pore-size controlled nanoporous BiVO4 photoanodes, and confirmed that the optimum pore-size distributions could effectively absorb visible light through light diffraction and confinement functions. Abstract : We demonstrate a facile method for the rational fabrication of pore-size controlled nanoporous BiVO4 photoanodes, and confirmed that the optimum pore-size distributions could effectively absorb visible light through light diffraction and confinement functions. Furthermore, in situ X-ray photoelectron spectroscopy (XPS) reveals more efficient photoexcited electron–hole separation than conventional particle films, induced by light confinement and rapid charge transfer in the inter-crossed worm-like structures.